A two-hashing table multiple string pattern matching algorithm - Khancome, Chouvalit; Boonjing, Veera; Chanvarasuth, Pisit (My University, 2013)
Multiple string pattern matching is one of many approaches to simultaneously search occurrences of a large number of patterns in a given text. In this paper, a new solution to this problem is presented by using two-hashing tables to minimize attempting times. This solution, called Two-Hashing Table Multiple String Patterns Matching Algorithm (Two-HT-MSPMA), is suitable for very long length of minimum pattern length. Its time complexity is more efficient than classic algorithms. Empirical results showed that its attempting times were less than of traditional algorithms. © 2013 IEEE.
Keywords: Exact String Matching; Hashing Data Structure; Pattern Detection Algorithm; Static Dictionary Matching